Invasive Coronary Angiography has Limited Diagnostic Accuracy for Detecting Reduction of Myocardial Perfusion Assessed by Cardiac Magnetic Resonance - Székely, Anna E.; Akil Engblom, Shahnaz; Hedeer, Fredrik; Kellman, Peter; Carlsson, Marcus; Erlinge, David ; 0000-0003-3042-5766; Mohammad, Moman A. ; 0000-0003-4242-9801; Arheden, Håkan; Engblom, Henrik (American Journal of Cardiology, 2025)
The relationship between degree of coronary artery stenosis and its effect on myocardial perfusion is complex and constitutes a clinical challenge. The aim of this study was to assess diagnostic accuracy of visual assessment of invasive coronary angiography (ICA) for detecting reduced myocardial perfusion determined by quantitative first-pass perfusion (qFPP) cardiac magnetic resonance (CMR) in patients with suspected or established chronic coronary syndrome (CCS). Forty-nine patients with suspected or established CCS were included from the elective ICA list in this prospective, observational study and underwent qFPP CMR prior to ICA. Myocardial perfusion at stress and myocardial perfusion reserve (MPR) were assessed for each vessel territory. Myocardial perfusion at stress <2.0 ml/min/g and MPR <2.4 were considered abnormal. Visually assessed coronary artery stenoses from ICA were considered significant if ≥70%. Sensitivity and specificity of visual assessment of ICA for detecting significant reduction of myocardial perfusion ranged between 32%-41% and 70%-76% on a per vessel level depending on myocardial perfusion measure used as reference. Accuracy ranged between 0.48-0.64. In 59%-68% of vessel territories with reduced stress perfusion or MPR, no significant stenosis was found. Thus, visual assessment of ICA has limited diagnostic accuracy for detecting significant reduction of myocardial perfusion assessed by qFPP CMR in patients with suspected or established CCS. Hence, quantitative myocardial perfusion is required when evaluating the cause of angina to distinguish between coronary stenosis, microvascular dysfunction and non-cardiac causes of chest pain.
Keywords: cardiac magnetic resonance; coronary artery disease; functional imaging; invasive coronary angiography; myocardial perfusion